Non-psychotic psychiatric disorders in persons who have experienced psychosocial stress in terms of military conflict. - L. M. Yuryeva; T. Y. Shusterman; E. O. Likholetov (Medičnì Perspektivi, 2019)
Partners of military veterans with post-traumatic stress disorder (PTSD) and other non-psychotic psychiatric disorders can develop difficulties with stress, well-being, and secondary trauma. There are various interventions involving partners, but not many of them give due attention to their well-being. The purpose of this article was to conduct a systematic literature review of a number of interventions with analysis of the results. A systematic literature search was conducted, as a result of which 25 interventions were selected for analysis. The criteria for selecting interventions were the presence of PTSD in the veteran, the partner’s participation in the intervention, and the focus of the intervention on improving the well-being of the partners themselves. Group interventions, boarding classes, family therapies and retreats were the main types of interventions. 21 studies reported well-being results from randomized controlled trials (RCT), preliminary evaluations and clinical cases. Most interventions reported improvements in partner well-being, although reliable, controlled trials were insufficient. Only a small number of interventions were aimed solely at partners. The most common feature of the interventions was psycho-educational work with an emphasis on topics such as communication, problem solving, and regulation of emotions. Most of the works describe the advantages of group processes (social support and normalization) among partners who shared experience with each other. Thus, the existing range of formats of measures to improve the well-being of military partners should be expanded through more reliable experimental studies aimed directly at the well-being of partners. A subsequent study of their effectiveness can serve as a powerful resource for further interventions not only for veterans, but also for the partners themselves.